Adverse drug reactions reporting: knowledge and opinion of general public in Penang, Malaysia - Elkalmi, Ramadan Mohamed Mahmod; Hassali, Mohamed Azmi; Al-lela, Omer Qutaiba; Awadh, Ammar Ihsan Jawad; Al-Shami, Abdul Kareem; Jamshed, Shazia Qasim (Canadian Society for Pharmaceutical Sciences, 2013)
Objective: The objective of this study was to explore the knowledge of the general population towards ADR and their reporting system. Methods: An anonymous, self-administered questionnaire (15 items) was designed. The questionnaire was subjected to face validity and content validity. The reliability coefficient was found to be 0.71. This study recruited proportionately large convenience sample of the general public in Penang. Interviews using a structured questionnaire were conducted over a week period in August 2009. The recommended sample size was calculated to be 368. Results: Three hundred thirty-four responses were received. Slightly more than half of the respondents were in the age group of 18-25 years (53.6%; n = 179). When asked about the sources of their medication majority of them reported medical doctor (85.6%), whereas small number (34.7%) reported community pharmacists as sources of medications. Three-quarter of the respondents (77.2%) get their information about the side-effects of drugs from physicians, followed by pharmacist (44.6%). More than half of the respondents (65.6%, n = 219) reported unawareness about the existence of ADR center set up by the Ministry of Health. Conclusion: Respondents reflected inadequate knowledge on ADR reporting. This needs to be corrected as the trend of future pharmacovigilance is toward the patient. Moreover, the new trend seems to be more appropriate as the patient is the group of the people who are directly affected from the ADR of a particular drug and not the health-care providers. Furthermore, the patient will be informed about the economic implications of not reporting ADR. It is recommended that government agencies, like MADRAC needs to find ways to increase patient- reported ADR cases.